(untitled) (Journal of Invasive and Clinical Cardiology, 2024)
Wide availability of recreational drugs, like amphetamine, cocaine, cannabis etc has spread out these drugs to all classes and age groups in the society of Bangladesh. Among them association cocaine and cannabis with acute myocardial infarction has been well established. But the popular drug, amphetamine, which is available in tablet form containing the active ingredient named 3,4 methylenedioxymethamphetamine (MDMA), has been reported to have significant cardiac and CNS toxicity. Repeated angina, even myocardial infarction due to active coronary vasospasm and accelerated atherothrombosis in amphetamine abusers has been reported in several case studies worldwide. But, only a few cases has been reported in Bangladesh. Here we present a case of acute myocardial infarction in a amphetamine abuser with low 10 years ASCVD risk. J Inv Clin Cardiol 2023; 5(2): 53-55